2021
DOI: 10.3390/app112210929
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxy-5,6-epoxy-β-ionone Isolated from Invasive Harmful Brown Seaweed Sargassum Horneri Protects MH-S Mouse Lung Cells from Urban Particulate Matter-Induced Inflammation

Abstract: Air pollution is a process that mixes pollutants into the atmosphere, which is potentially harmful to humans and causes negative impacts on the surrounding environment (biotic and abiotic). The negative health effects associated with air pollution have been reported from both indoor and outdoor environments. Specifically, dust storms originating in Chinese and Mongolian desert areas introduce significant amounts of particulate matter (PM) to the Korean atmosphere. Previously, several studies reported that urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In our previous study, UPM 1648a affected keratinocytes by regulating p38 and NF-κB pathways [64,65]. Other studies have shown that endotoxin present in UPM increases TLR4-mediated inflammatory responses in murine alveolar macrophages [66,67]. Here, NF-κB is one of the significant downstream regulators of TLR4 signaling.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our previous study, UPM 1648a affected keratinocytes by regulating p38 and NF-κB pathways [64,65]. Other studies have shown that endotoxin present in UPM increases TLR4-mediated inflammatory responses in murine alveolar macrophages [66,67]. Here, NF-κB is one of the significant downstream regulators of TLR4 signaling.…”
Section: Discussionmentioning
confidence: 80%
“…Here, NF-κB is one of the significant downstream regulators of TLR4 signaling. It has also been reported that several substances exhibit efficacy in alleviating UPM-induced lung injury through the inhibition of NF-κB and TLR4 [66,68]. Likewise, Pj-EE-CF suppressed UPM 1648a-induced phosphorylation of NF-κB signal molecules (IκBα, p50, p65), alleviating lung inflammation and injury [65,69].…”
Section: Discussionmentioning
confidence: 94%